2018
DOI: 10.1111/acel.12793
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and aging: A role for the mitochondrial transition pore?

Abstract: SummaryThe cellular mechanisms responsible for aging are poorly understood. Aging is considered as a degenerative process induced by the accumulation of cellular lesions leading progressively to organ dysfunction and death. The free radical theory of aging has long been considered the most relevant to explain the mechanisms of aging. As the mitochondrion is an important source of reactive oxygen species (ROS), this organelle is regarded as a key intracellular player in this process and a large amount of data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 214 publications
1
85
0
Order By: Relevance
“…47 Mitochondria play a vital role in β-oxidation of FFAs, and mitochondrial dysfunctions, such as extensive mitochondrial permeability transition pore (mPTP) opening and impaired respiratory functions, lead to excess ROS production causing apoptotic cell deaths. 48 Das et al have demonstrated that palmitic acid induces mitochondrial fragmentation, calcium overload, and mPTP opening, but melatonin treatment (1 mmol/L for 30 minutes) inhibits these effects in HepG2 cells in vitro. 49 HFD decreased mitochondrial enzyme activities in mice, such as cytochrome C oxidase and pyruvate dehydrogenase, but melatonin administration (10 or 20 mg/kg daily for 4 weeks, i.p.…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…47 Mitochondria play a vital role in β-oxidation of FFAs, and mitochondrial dysfunctions, such as extensive mitochondrial permeability transition pore (mPTP) opening and impaired respiratory functions, lead to excess ROS production causing apoptotic cell deaths. 48 Das et al have demonstrated that palmitic acid induces mitochondrial fragmentation, calcium overload, and mPTP opening, but melatonin treatment (1 mmol/L for 30 minutes) inhibits these effects in HepG2 cells in vitro. 49 HFD decreased mitochondrial enzyme activities in mice, such as cytochrome C oxidase and pyruvate dehydrogenase, but melatonin administration (10 or 20 mg/kg daily for 4 weeks, i.p.…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…However, these models have limited application to the aging liver due to differences in their respective molecular and metabolic phenotypes. Since oxidative stress and mitochondrial dysfunction are considered to be critical for senescence and aging [6,11,24,25], we have developed a protocol that produces these changes to induce premature cellular senescence in nontransformed AML12 hepatic cells to study hepatic aging in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Senescent cells also had increased mitochondrial activity compared to control cells. However, this increased activity did not lead to more ATP production due to concomitant increases in basal uncoupling and proton leakage, which are hallmarks of senescent cells [1,25,27,29]. These findings thus explains the reason why there is increased AMP:ATP ratio leading to the AMPK activation often found in senescent cells [1,27,29].…”
Section: Senescent Cells Are Metabolically Hyperactive and Display A mentioning
confidence: 97%
See 1 more Smart Citation
“…mPT induction is closely related to mitochondrial oxidant release; interventions that augment antioxidant defenses and/or decrease the rate of oxidant release are expected to decrease the probability of mPT (reviewed in Kowaltowski et al, 2001;Figueira et al, 2013;Vercesi et al, 2018). Susceptibility to mPT also increases with age in several tissues (Panel et al, 2018). The same is observed with conditions that promote unhealthy aging, such as high-fat diets, obesity and diabetes (Littlejohns et al, 2014;Castillo et al, 2019;Anderson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%